Behavior of Indonesian Nurses Toward Non-Reported Needle Stick Injury in Saudi Arabia: A Phenomenological Study - Akhir Fahruddin; Yayi Suryo Prabandari; Martinus Sutena; Nurul Uswatin (Jurnal Berita Ilmu Keperawatan, 2023)
Non-reported needle stick injury (NSI) is still a major problem faced by nurses when working in health services in Saudi Arabia viewed from the perspective of occupational health and safety (OHS). Knowing the behavior of nurses in the workplace can have implications for the OHS culture. Objective: To explore the behavior of Indonesian nurses towards non-reported NSI in health services in Saudi Arabia. This study used a qualitative method with a phenomenological approach. The research subjects used typical case sampling of 12 Indonesian nurses who had work experience regarding NSI. In-depth interviews with structured questions were conducted with respondents following guidelines for data analysis using a seven step analysis by Colaizzi and Nvivo software. There were 13 categories from 4 themes found in this research about knowledge, behavior and skills also management of exposure and post exposure. The behavior of Indonesian nurses towards non-reported needle stick injury based on experience has been carried out even though the behavior, especially knowledge, attitude and skills policy on management of needle stick injury needs improvement.